Tipologi Jaringan Wacana dan Komunikator Publik dalam Berita Omicron Baru di Media Online - Paulus Angre Edvra; Nyarwi Ahmad (Jurnal Riset Komunikasi (JURKOM), 2023)
The first case of Omicron BA.4 and BA.5 subvariants on 9 June 2022 confirmed by the Government has propelled a news explosion. This article examines what discourses constructed by public communicators who addressed this case, as reported by the online media, and who are they? We analyze online news related to this issue published in between 9 and 16 June 2022 using the discourse network analysis. We found 15 categories of discourse related to this case advocated by five types of public communicators. They consist of 25 types of specific actors. While some of them advocated types of discourses identified by Ali and Eriyanto (2020), most of them formulated new discourses when they addressed this case. Our research also revealed that public communicators that represent the Government do not have a single discourse when they managed this case. This hints that the Government lacked an integrated public communication strategy in handling this case